Diagnostik Kesulitan Belajar Matematika Siswa Pada Materi Operasi Hitung Penjumlahan dan Pengurangan - Astuti, Ninik; Umar, Firdaniati; Handayani, Resky; Nurjannah, Nurjannah (Tadris Matematika, 2024)
This research was conducted at SDN 28 Pakkita, which is in Salohe, Kec. East Sinjai, Kab. Sinjai, Prov. South Sulawesi. The purpose of this study was to describe students' learning difficulties in mathematics about addition and subtraction of integers. This research method is descriptive qualitative research method. The subjects in this study were two third grade students of SDN 28 Pakkita. The data collection techniques used in this study were observation, diagnostic tests, and interviews. The results of this study indicate that the subject already understands the concept of addition operations by storing and subtracting by borrowing but the subject is less careful in working on the questions given while the learning difficulties experienced by subjects are difficulties in counting so that subjects have difficulty in working on the questions. given question. Efforts are made to overcome learning difficulties experienced by students, namely teachers need to understand the characteristics of their students and provide motivation so that they can have a passion for learning mathematics. and Efforts that parents can do at home are to guide and train children so that they can master little by little the material being taught, especially at school.